Post-marketing safety surveillance for the recombinant zoster vaccine (Shingrix), vaccine adverse event reporting system, United States, October 2017–April 2024 - Yamin Shu; Wenxin Cheng; Xucheng He; Liu Huang; Wei Chen; Qilin Zhang (Preventive Medicine Reports)
Background: Recombinant zoster vaccine (RZV), received its first marketing authorization in October 2017 to prevent herpes zoster and its complications in older adults. The purpose of this study was to provide comprehensively worldwide post-marketing safety information about RZV using data from the Vaccine Adverse Event Reporting System (VAERS). Methods: We searched for and analyzed adverse event (AE) reports of RZV submitted to U.S. VAERS between October 20, 2017 and April 26, 2024. Descriptive analyses included sex, age, time-to-onset, seriousness, most commonly reported AEs, AE of special interest, and cause of death. The empirical Bayesian data mining was employed to identify potential disproportionalities in reporting. Results: During the study period, 1,279,596 AE reports for vaccines were received by VAERS after excluding any duplicates, including 66,849 reports specifically related to RZV. Most reports were classified as non-serious (97.3 %). Among reports with age or sex reported, individuals were mainly 50–79 years (71.2 %) and females (63.1 %). The most commonly reported AEs included injection site reactions, pyrexia, chills, headache and fatigue. A total of 86 reports documenting deaths were identified following RZV vaccination. In addition to cardiovascular events and falls, Guillain-Barre syndrome was the most common cause of death. The median TTO for RZV-related AEs was 1 day in all cohort groups over 50 years old. Conclusion: The safety profile of RZV, based on the large sample post-marketing use, was reassuring and consistent with that observed in clinical trials. Further studies are needed to continue generating real-world safety data and further characterize RZV-AE pairs systematically.